2017
DOI: 10.1111/ecoj.12314
|View full text |Cite
|
Sign up to set email alerts
|

International Trends in Technological Progress: Evidence from Patent Citations, 1980–2011

Abstract: We analyse cross‐country trends in several aspects of technological progress during 1980–2011 by examining the US patent citations data. Our estimation results on patent quality and citation lags relative to the US reveal the following. The emerging Asian economies of Korea, Taiwan and China have achieved substantial catch‐up. In the case of Korea and Taiwan, progress has been made in both patent quality and citation lags. China has achieved improvement in patent quality but not in citation lag. In contrast, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…While Sonn and Storper (2008) draw similar conclusions, their analysis is based on patents only up to 1997, and it is precisely around this period when the IT revolution took off and, moreover, we began to see a meteoric rise in both the number of inventions and the diversity of inventors (e.g. Kwon, Lee, and Lee 2017). Another important difference is that Sonn and Storper select control patents only at the three-digit primary level, but as TFK note, the results are sensitive to the level of disaggregation.…”
Section: Introductionmentioning
confidence: 81%
“…While Sonn and Storper (2008) draw similar conclusions, their analysis is based on patents only up to 1997, and it is precisely around this period when the IT revolution took off and, moreover, we began to see a meteoric rise in both the number of inventions and the diversity of inventors (e.g. Kwon, Lee, and Lee 2017). Another important difference is that Sonn and Storper select control patents only at the three-digit primary level, but as TFK note, the results are sensitive to the level of disaggregation.…”
Section: Introductionmentioning
confidence: 81%
“…However, empirical insights on the timing of entry remain largely qualitative in the catch-up literature (Lee and Malerba, 2017;Perez and Soete, 1988). Kwon, Lee & Lee (2017) is the first to systematically quantify the catching-up process by investigating the time needed for inventors of a particular country to cite an invention from technological frontier. They showed that Korea, Israel and Taiwan managed to narrow the gap with technological frontier, whereas similar progress is not observed in China and India.…”
Section: Windows Of Opportunity and The Timing Of Entrymentioning
confidence: 99%
“…We only focus on breakthroughs which are adopted more than 20 times as to be able to apply a threshold for the impacts of new technologies following Pezzoni et al (2019). Moreover, we focus on breakthroughs introduced by inventors from United States to proxy new technologies developed at the technology frontier following Kwon et al (2017). As a robustness check, we also use breakthroughs introduced by inventors from Germany and Japan as a robustness check.…”
Section: Econometric Modelmentioning
confidence: 99%
“…The development of 5G could create considerable business opportunities [10], and optical networks are an indispensable type of infrastructure for the development of 5G; therefore, the incorporation of wireless and optical communication into access networks is an inevitable future development trend. Additionally, patents are the manifestation of industrialized technologies; they are beneficial for businesses to achieve monopoly in the technology market, and could serve as indicators for technology development trends [11][12][13]. Therefore, in the current study, the researchers identified key technologies and development trends in 5G optical networks by analyzing the patent data and using a network analysis method.…”
Section: Introductionmentioning
confidence: 99%